The Effect of Independence And Competence On Audit Quality With Professional Skepticism As A Moderating Variable - Bagus Arif Budiman Yunas; Ni Nyoman Alit Triani (Faculty of Economics, Merdeka University Surabaya, Indonesia, 2022)
The purpose of this study is to see how independence and competence interact with professional skepticism as a moderating variable. A quantitative approach was adopted, utilizing data collection technique of questionnaires. The participants in this study were auditors working for all public accounting companies in Surabaya. A total of 129 responders were chosen from a pool of 230 auditors. Purposive sampling was utilized to collect data. The descriptive statistics and SPSS program were utilized to analyze the data in this study. The findings revealed that audit quality was positively influenced by independence, competence, and professional skepticism. Professional skepticism also enhances the relationship between independence and quality, but it cannot strengthen the relationship between competence and quality.